2023
DOI: 10.1371/journal.pone.0287042
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of antimicrobial resistance knowledge, attitudes, and practices: Current evidence to build a strong national antimicrobial drug resistance narrative in Ethiopia

Abstract: Antimicrobial resistance (AMR) is a silent pandemic that has claimed millions of lives, and resulted in long-term disabilities, limited treatment options, and high economic costs associated with the healthcare burden. Given the rising prevalence of AMR, which is expected to pose a challenge to current empirical antibiotic treatment strategies, we sought to summarize the available data on knowledge, attitudes, and practices regarding AMR in Ethiopia. Articles were searched in international electronic databases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…CD4 T-cell counts of [200–499] and <200 cells/mm 3 were reported in our study, and similar counts are most likely reported in cases of development of OIs. This result is reasonable as CD4 T-cells play critical roles in the induction of both humoral and cellular immunity to combat OIs [ 1 ]. Comparatively, other authors found that PLWHA with a CD4 T-cell count of 200 cells/mm 3 were at higher risk of developing advanced forms of OIs such as pulmonary TB [ 51 ].…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…CD4 T-cell counts of [200–499] and <200 cells/mm 3 were reported in our study, and similar counts are most likely reported in cases of development of OIs. This result is reasonable as CD4 T-cells play critical roles in the induction of both humoral and cellular immunity to combat OIs [ 1 ]. Comparatively, other authors found that PLWHA with a CD4 T-cell count of 200 cells/mm 3 were at higher risk of developing advanced forms of OIs such as pulmonary TB [ 51 ].…”
Section: Discussionmentioning
confidence: 73%
“…There is regularly a shortage of ARVs experienced in Gabon, and that might assuredly constitute a significant contributor and possible explanation for the high rates of OIs. Furthermore, starting ART at later stages of HIV infection, on the one hand, and the disparity observed in the level of engagement in HIV care facilities in poor countries or/and resource-limited areas, on the other hand, limit the effectiveness of the administered therapy [ 1 , 23 ]. Additionally, the emerging or increasing levels of HIV drug resistance to NNRTIs in resource-limited countries could also be considered as restraining factors [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations